An improved scheme for measuring 13C spin-lattice relaxation time: Targeting systems with marked difference in phase mobility or proton density. (August 2019) - Wang, Ning; Tang, Dandan; Shu, Jie
Abstract: A novel scheme, named DP-Torchia was developed to measure the spin-lattice relaxation time ( T 1 ) of low abundant nuclei, such as 13 C. Apart from the common samples that are suitable for the traditional 13 C T 1 methods, DP-Torchia is also designed for the mixtures or materials containing domains with markedly different local mobility or sharply distinct proton distribution. Through the tests of L-alanine/adamantane (Ala/Ada) mixture as well as the polymer blend of polyvinyl alcohol and polytetrafluoroethylene (PVA/PTFE), the performances of three methods are compared, including inverse-recovery (IR), Torchia and DP-Torchia. It is demonstrated that the results measured using DP-Torchia are in accordance with those of Torchia and IR methods, with the relative deviation of less than 3% for Ala/Ada mixture, while 1.5% for PVA/PTFE blend. Moreover, DP-Torchia consumes less experimental time than that of traditional methods, saving one-third of the traditional measuring time for Ala/Ada mixture, while consuming 6 h less measuring time than that of the traditional methods for PVA/PTFE blend. Compared with the common used methods, inverse-recovery and Torchia, DP-Torchia consumes less experimental time with more tolerance to the measured samples. Those favorable performances imply that DP-Torchia method has potential to become a routine tool for measuring 13 C T 1 values, especially for the materials with marked difference in phase mobility or proton density for industrial and scientific research. Highlights: An improved SSNMR method, named DP-Torchia, is proposed for measuring 13 C T1 . Besides the samples that are suitable for traditional 13 C T1 methods, DP-Torchia is also designed for the materials containing domains with different local mobility or distinct proton distribution. The accuracy of DP-Torchia result is identical to that of traditional methods. DP-Torchia consumes shorter time with less work of data processing.